Characteristics and treatment in patient with Vaginismus in East Java Indonesia - Kurniawati, Eighty Mardiyan; Hardianto, Gatut; Paraton, Hari; Setyo Hadi, Tri Hastono; Widyasari, Anis; Rahmawati, Nur Anisah (Indonesian Journal of Obstetrics and Gynecology, 2025)
Background - Vaginismus is still an under-researched case of women's health despite its universal prevalence. Aim -This study aims to explore the characteristics of vaginismus in East Java Indonesia. Methods- The subjects in this study were all new female patients with Vaginismus was found in a single hospital - East Java Indonesia in 2022. The data used in this study are secondary data obtained from the medical records. Descriptive data are presented as numbers and percentages for categorical data. Results – Vaginismus was found in a single hospital - East Java Indonesia. Based on medical record data, throughout 2022 there will be 60 patients with a diagnosis of Genito Pelvic Pain Penetration Disorder (GPPPD). The results of the assessment of patient characteristics showed that almost all patients were of reproductive age. Most of the respondents have been married for more than 1 year. Management is carried out independently and collaboratively. A total of 60 patients underwent anamnesis and physical examination. Complaints experienced by patients are failure to penetrate. Treatment was done using Botox injections, dilatation, hymenectomy, and consultation to psychiatrist and andrologist. Conclusion - Management in cases of Vaginismus requires cross-professional collaboration such as psychiatrists and andrology. The treatment given also tends to be complex.